2014
DOI: 10.1186/cc13859
|View full text |Cite
|
Sign up to set email alerts
|

Early fluid loading in acute respiratory distress syndrome with septic shock deteriorates lung aeration without impairing arterial oxygenation: a lung ultrasound observational study

Abstract: IntroductionThe study was designed to assess the impact of fluid loading on lung aeration, oxygenation and hemodynamics in patients with septic shock and acute respiratory distress syndrome (ARDS).MethodsDuring a 1-year period, a prospective observational study was performed in 32 patients with septic shock and ARDS. Cardiorespiratory parameters were measured using Swan Ganz (n = 29) or PiCCO catheters (n = 3). Lung aeration and regional pulmonary blood flows were measured using bedside transthoracic ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 40 publications
1
105
0
4
Order By: Relevance
“…Neovascularization is a characteristic feature of tumor consolidation, which accounts for the low-impedance flow. However, other researchers also have found that pulmonary blood flow persists within the consolidations caused by ARDS or a diffuse alveolar hemorrhage [55, 56]. These results indicate that the hemodynamic changes observed in the regional pulmonary artery during lung consolidation are complex.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Neovascularization is a characteristic feature of tumor consolidation, which accounts for the low-impedance flow. However, other researchers also have found that pulmonary blood flow persists within the consolidations caused by ARDS or a diffuse alveolar hemorrhage [55, 56]. These results indicate that the hemodynamic changes observed in the regional pulmonary artery during lung consolidation are complex.…”
Section: Introductionmentioning
confidence: 85%
“…Lastly, LUS scoring systems based on the A line, B line, and lung consolidation have been applied for the quantitative monitoring of lung aeration and aeration changes [28, 55, 60, 61]. All these scoring systems divide lung aeration into four ultrasound patterns for the assessment of aeration and re-aeration observed on LUS.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, while providing unessential or dangerous statements, this Commentary seems to overlook the strong evidence behind the use of semiquantitative LUS in critically ill patients of any age. In fact, several US scores, carrying all of the intrinsic characteristics due to their semiquantitative nature and being even simpler than the neonatal one, have been validated against a multitude of techniques (Table ), confirming their usefulness despite their intrinsic limitations . Table is not comprehensive, but it is out of the scope of this article to list all LUS validation studies.…”
Section: Examples Of Studies Validating Lus Scores Against Various Mementioning
confidence: 97%
“…Der bisher nicht geklärten Frage, welche Folgen eine Albumin-Gabe bei schwerer Sepsis hat, ging eine kürzlich publizierte italienische randomi sierte, offene und multizentrische Studie nach [5] anzupassen und nicht in die Gefahr einer prog nostisch ungünstigen Hypervolämie zu kommen [25,26].…”
Section: Klinische Relevanzunclassified